Dynamic forced shear characteristics of Ti-6Al-4V alloy using flat hat-shaped specimen. (15th October 2020) - Ran, Chun; Liu, Qingqing; Chen, Pengwan; Chen, Qi
Highlights: ASB nucleates after the maximum stress and drastic stress drop corresponds to the initiation and propagation of crack; The microstructure gets increasingly refined due to the occurrence of dislocations, stacking faults and cell structures; Thermal softening might not have had a pronounced effect on the onset of ASB and DRX formation; "Cohesive fracture" can be identified as the dynamic failure mechanism of Ti-6Al-4V alloy. Abstract: The relation between stress collapse and nucleation of adiabatic shear band (ASB) remains incompletely understood. To further understand this topic, the evolution of shear deformation of Ti-6Al-4V alloy under forced shear loading is systematically investigated using digital image correlation (DIC) technique. DIC results indicate that ASB nucleates after the maximum stress and drastic stress drop corresponds to the initiation and propagation of crack, and the forced shear process can be divided into homogeneous, inhomogeneous and highly localized deformation stages. Numerical simulation results suggest that thermal softening might not have had a pronounced effect on the onset of adiabatic shear band and dynamic recrystallization formation. "Cohesive fracture" can be identified as the dynamic failure mechanism for Ti-6Al-4V alloy on the basis of the crack propagation features, and the microstructure gets increasingly refined due to the occurrence of dislocations, stacking faults and cell structures.